Prospects of a manufacturing industry for the platinum group metals in South Africa - Barry, Shaun Downing (My University, 2016)
South Africa is the largest primary producer of platinum-group metals (PGMs) in the world. It is estimated that only 2.1 per cent of the 153711 kg of total sales for 1993 was beneficiated locally. Potential value added foreign exchange earnings and employment opportunities. therefore. are being forfeited. This study identifies prospective areas of development in the major sectors of application of PGMs namely: autocatalysts; chemical and allied industries; electrical and electronics sectors; jewellery and coinage fabricators. The methodology of intensity of use (IOU) is first discussed. ThIs is followed by an analysts of South Africa's production and sales of PGMs. The body of the report is an empirical study of the IOU of platinum and palladium to establish a world outlook for these metals in their applications. Finally, the more lucrative of these applications are discussed in the light of South Africa's participiltion and competitiveness in the world market. The conclusions are firstly, that the established autocatalyst industry has the best prospect for growth and expansion. Secondly, the electrical application of platinum in fuel cells has potential depending on the level of government funding and support for a R&D programme. The third finding is that the electronics and jewellery industries have development potential on condition that resistance to market entry can be overcome by reduced public policy costs. Possible violation of GATT agreements may be avoided for these applications by world free trade co-operation.
A project report submitted to the faculty of Engineering, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering. Johannesburg, 1994.
Keywords: Platinum industry -- South Africa.; Electrodes, Platinum.; Jewelry trade -- South Africa.; Platinum catalysts.